Tai chi training reduces self-report of inattention in healthy young adults - Converse, Alexander K.; Ahlers, Elizabeth O.; Travers, Brittany G.; Davidson, Richard J. (Frontiers in Human Neuroscience, 2014)
It is important to identify effective non-pharmacological alternatives to stimulant medications that reduce symptoms of attention deficit hyperactivity disorder (ADHD). In this study of healthy young adults, we measured the effects of training in tai chi, which involves mindful attention to the body during movement. Using a non-randomized, controlled, parallel design, students in a 15-week introductory tai chi course (n=28) and control participants (n=44) were tested for ADHD indicators and cognitive function at three points over the course of the 15 weeks. The tai chi students' self-report of attention, but not hyperactivity-impulsivity, improved compared to controls. At baseline, inattention correlated positively with reaction time variability in an affective go/no-go task across all participants, and improvements in attention correlated with reductions in reaction time variability across the tai chi students. Affective bias changed in the tai chi students, as reaction times to positive- and negative-valenced words equalized over time. These results converge to suggest that tai chi training may help improve attention in healthy young adults. Further studies are needed to confirm these results and to evaluate tai chi as therapy for individuals with ADHD.